India's increasing skill premium: role of demand and supply - Mehtabul Azam (Institute for the Study of Labor (IZA), 2009)
The tertiary-secondary (college-high school) wage premium has been increasing in India over the past decade, but the increase differs across age groups. The increase in wage premium has been driven mostly by younger age groups, while older age groups have not experienced any significant increase. This paper uses the demand and supply model with imperfect substitution across age groups developed in Card and Lemieux (2001) to explain the uneven increase in the wage premium across age groups in India. The findings of this paper are that the increase in the wage premium has come mostly from demand shifts in favor of workers with a tertiary education. More importantly, the demand shifts occurred in both the 1980s and 1990s. Relative supply has played an important role not only determining the extent of increase in wage premium, but also its timing. The increase in relative supply of tertiary workers during 1983-1993 offset the demand shift, limiting the wage premium increase. But during 1993-1999, the growth rate of the relative supply of tertiary workers decelerated, while relative supply was virtually stagnant during 1999-2004. Both of these periods saw an increase in the wage premium as the countervailing supply shift was weak.
urn:nbn:de:101:1-2009021077
Keywords: J20; J23; J31; 330; India; wage premium; tertiary (college); secondary (high school); Lohnstruktur; Bildungsniveau; Qualifikation; Hochqualifizierte Arbeitskräfte; Arbeitsnachfrage; Altersgruppe; Indien